Hand and Wrist Injuries Among Collegiate Athletes: The Role of Sex and Competition on Injury Rates and Severity. Issue 12 (15th December 2020) - Simpson, Andrew M.; Donato, Daniel P.; Veith, Jacob; Magno-Padron, David; Agarwal, Jayant P.
Background: There is a high incidence of hand and wrist injuries in athletes participating in collegiate sports, but there is little information published characterizing them. Purpose: To characterize hand and wrist injuries in collegiate athletes using a large national database. Study Design: Descriptive epidemiology study. Methods: This retrospective cross-sectional analysis was designed using data from the National Collegiate Athletic Association (NCAA) Injury Surveillance Program database to identify hand and wrist injuries (exclusive of any radial or ulnar fractures) in male and female collegiate athletes participating in NCAA Division I, II, and III sports from 2004 to 2015. Descriptive analyses were performed on stratified data to examine the associations between these injuries and sport, event type, and sex. Results: Men's ice hockey (8.25 per 10, 000 athlete-exposures [AEs]) and women's ice hockey (8.21 per 10, 000 AEs) had the highest rate of hand and wrist injuries in all exposures. In every sport except women's gymnastics ( P = .107), injuries were more commonly sustained during competition rather than during practice. Ligamentous injury to the phalynx was the most commonly sustained injury overall (1.416 per 10, 000 AEs), and a metacarpal fracture was the most commonly sustained hand or wrist fracture (0.507 per 10, 000 AEs). Injuries sustained during men's wrestling (14.08 days) and women's gymnastics (10.39 days) incurred the most time lost from sport. Surgery for hand and wrist injuries was most commonly required for men's football (0.413 per 10, 000 AEs) and women's field hockey (0.404 per 10, 000 AEs). Conclusion: Hand and wrist injuries were common among collegiate athletes. Male athletes experienced injuries with more frequency and severity. Injuries occurred more commonly during competition. While the majority of injuries were minor and did not require surgery, certain sports conferred a much higher risk of significant injuries requiring a surgical intervention.